Silenced sextet : six nineteenth-century Canadian women novelists - MacMillan, Carrie, 1945- (McGill-Queen's University Press, 1992)
The Canadian publishing industry burgeoned during the late nineteenth century and Canadian poets and novelists began to gain international recognition. Twentieth-century literary scholars, however, have tended to focus on just a few of the writers of this vital expansive period. Many other writers with strong critical reputations and/or popular followings -- a good proportion of whom were women -- have been virtually lost to us.